STUDI ANALISIS KEMAMPUAN MEMBACA DAN MENULIS PESERTA DIDIK KELAS II - Maria Yosefina Ule; Lydia Ersta Kusumaningtyas; Ratna Widyaningrum (Widya Wacana: Jurnal Ilmiah, 2023)
The purpose of this research are: 1) to analyze the reading and writing abilities of class II B students at Mojosongo VI State Elementary School and 2) to determine the factors that influence the reading and writing abilities of class II B students at Mojosongo VI State Elementary School, Surakarta. This research uses descriptive qualitative research. As for data sources, 1) primary data was obtained from interviews and documentation and 2) secondary data was obtained from teacher data and student data for class II B at SD Negeri Mojosongo VI Surakarta. The research subjects were: 1) class II B students, 2) class II B teachers, and 3) parents of class II B students and the research objects were obtained from documentation at SD Negeri Mojosongo VI Surakarta. The data collection techniques used were: 1) interviews, 2) observation, and 3) documentation. The validity of the data used is: 1) source triangulation and 2) technical triangulation. Data analysis, namely: 1) data collection, 2) data reduction, 3) data presentation, and 4) drawing conclusions. Based on the results of interviews and observations, it shows that based on students' reading and writing abilities there are still difficulties, namely 1) difficulties when learning to read, namely: a) difficulty reading certain letters, b) difficulty pronouncing diphthong letter sounds, c) difficulty pronouncing letter sounds double consonants, d) difficulty distinguishing between letters such as the letters "p, q, and x", and e) difficulty reading syllables 2) difficulty when learning to write, namely: a) writing is not neat, b) not being careful when writing, c) difficulty writing when leaving a distance between one letter and another, d) there are scribbles in the writing, e) difficulty when writing example sentences and words from the blackboard, f) difficulty when copying example words and sentences from the blackboard, g) difficulty when imitating examples of words and sentences from the blackboard, h) difficulty when drawing circles, and i) difficulty when drawing circle shapes and 3) factors that influence students' reading and writing abilities, namely: 1) internal factors, namely: a ) interest and b) motivation and 2) external factors, namely: a) family environment and b) school environment. Keywords: Language, Reading Ability, Writing Ability